The Indian tax system as a fact of competitiveness - Aldeia, Susana (2020)
This paper seeks to study the corporate income tax law’s specifics of Indian companies and understand if it can to constitute a competitiveness factor for these businesses. The research makes a legal structure analysis of India Jurisdiction, it incorporates several Indian data sources: the Constitution of India and the Income-Tax Act of 1961. The results show that the Indian lawmaker is conservative on legislative changes. The law regulating the taxation of corporate profits dates back to 1961, and despite some amendments, it maintains over time. The fact that corporate tax rules remain stable over time represents predictability for investors, which is a very compelling competitiveness factor for business. However, this law presents some less positive features in some situations. The wording’s law is old, so sometimes it is challenging to interpret the legislator intention; it can means difficulties in compliance's law. Also, the law establishes particular rules for taxable bases’ determination on income tax corporate. It represents a duplication of accounting and tax rules, so, each entity has to prepare accounting and a tax statement.